MANAJEMEN PEMBELAJARAN UNTUK MENINGKATKAN MUTU PENDIDIKAN (PENELITIAN DI SMA AL-MUTTAQIN KOTA TASIKMALAYA) - Helmatillah; Ai Hilyatul Halimah; Imas Komalasari (An-Nahdliyyah: Jurnal Studi Keislaman, 2022)
Learning management is a management process, that includes planning, organizing, controlling, and evaluating activities related to the process of teachinglearners by incorporating various factors in it, in order to achieve educationalgoals and strive to improve the education quality. Education quality is educationthat can produce alumnus who have good character. And to produce student who have good character, then it needed to a good learning management too. This research aims to explore the problems about learning management to improve the education quality in Senior High School Al-Muttaqin Tasikmalaya City. This research uses descriptive qualitative research method. The method used to collect data is through observation, interviews, archive analysis and documentation.The process of data analysis in this research used interactive model analysis whichconsists of: data reduction, data presentation, and conclusion. Based on research results, it indicated that: (1) Learning managementprocess at Senior High School Al-Muttaqin Tasikmalaya City run well, with the implementation oflearning management according to the planning and organizing that have beendetermined; (2) The education quality standard that applied by Senior High School Al-Muttaqin Tasikmalaya City is increased continuously (3) The education quality of Senior High School Al-Muttaqin Kota Tasikmalaya has increased from year to year seen from the number of alumnus who have good achievement and able to continue to college level.